Pengaruh Financial Distress, Volatilitas Arus Kas , Firm Size, Leverage Terhadap Keputusan Hedging dengan Likuiditas Sebagai Pemoderasi - Tuti Yulianingsih; Hexana Sri Lastanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the context of global economic uncertainty, companies face significant exchange rate risks that can affect their cash flow stability and operational continuity. One strategy to manage this risk is through hedging, which has become increasingly relevant, particularly for companies involved in international trade. This study focuses on how financial distress, cash flow volatility, firm size, and leverage influence hedging decisions, with liquidity as a moderating variable. This research employs multiple linear regression analysis using data from the financial statements of automotive sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sample was selected using purposive sampling based on specific criteria. The results of the study show that financial distress, cash flow volatility, firm size, and leverage have a simultaneous and combined effect on hedging decisions. Financial distress and leverage have a positive and significant influence on hedging. Meanwhile, cash flow volatility and firm size have a positive but not significant influence on hedging decisions. Liquidity was found to only enhance the positive impact of financial distress, while the other three variables—cash flow volatility, firm size, and leverage—did not significantly strengthen the hedging decisions.